Epigenetics of Early Child Development - Murgatroyd, Chris; Spengler, Dietmar (Frontiers in Psychiatry, 2011)
Comprehensive clinical studies show that adverse conditions in early life can severely impact the developing brain and increase vulnerability to mood disorders later in life. During early postnatal life the brain exhibits high plasticity which allows environmental signals to alter the trajectories of rapidly developing circuits. Adversity in early life is able to shape the experience-dependent maturation of stress-regulating pathways underlying emotional functions and endocrine responses to stress, such as the hypothalamo-pituitary-adrenal (HPA) system, leading to long-lasting altered stress responsivity during adulthood. To date, the study of gene-environment interactions in the human population has been dominated by epidemiology. However, recent research in the neuroscience field is now advancing clinical studies by addressing specifically the mechanisms by which gene-environment interactions can predispose individuals towards psychopathology. To this end, appropriate animal models are being developed in which early environmental factors can be manipulated in a controlled manner. Here we will review recent studies performed with the common aim of understanding the effects of the early environment in shaping brain development and discuss the newly developing role of epigenetic mechanisms in translating early life conditions into long-lasting changes in gene expression underpinning brain functions. Particularly, we argue that epigenetic mechanisms can mediate the gene-environment dialogue in early life and give rise to persistent epigenetic programming of adult physiology and dysfunction eventually resulting in disease. Understanding how early life experiences can give raise to lasting epigenetic memories conferring increased risk for mental disorders, how they are maintained and how they could be reversed, is increasingly becoming a focus of modern psychiatry and should pave new guidelines for timely therapeutic interventions.